The meaning of Metallica ride the lyrics - Irwin, William 1970- (ECW, 2022)
"The first book to give Metallica's lyrics the care and contemplation they deserve More than 40 years since their formation, and 125 million albums later, Metallica is as relevant as ever. Much has been written about the band, but The Meaning of Metallica is the first book to focus exclusively on their lyrics. Their mighty guitar riffs and pounding drums are legendary, but Metallica's words match the intensity of their tunes. Lead singer James Hetfield writes rock poetry dealing with death, war, addiction, alienation, corruption, freedom, religion, and other weighty topics. Painting a rainbow of emotions with a deft palette, subtle but not obscure, Hetfield's lyrics deserve careful attention. A master of narrative, Metallica makes listeners care about a vast array of characters, from a vengeful God, to a suicidal teenager, to a man in mid-life crisis. The Meaning of Metallica is like a riveting conversation with a close friend. A thematic tour de force that traces Hetfield's lyrical development across the decades, this companion examines everything from deep cuts like "Confusion" to megahits like "Enter Sandman." Sure to spark debate and discussion, The Meaning of Metallica provides a close reading of lyrics dense with details and rich with allusions."
Keywords: Metallica -- Musikgruppe; Text; Rocksong; Metallica (Musical group); Rock musicians / United States / Biography; Heavy metal (Music) / United States / History and criticism; Musiciens rock / États-Unis / Biographies; Heavy metal (Musique) / États-Unis / Histoire et critique; Heavy metal (Music); Rock musicians; United States; collective biographies; Biographies; Criticism, interpretation, etc